Eliminating the Leaky Pipeline: Sustaining-Normalizing-Engendering Women's Careers as Academics, Researchers and Professionals in Engneering, Computers and the Sciences - Irene Kamberidou (Presentation at the UNICAFE Dissemination Conference "Beyond the Glass Ceiling: Women Academics in Engineering, Technology and Life Sciences across Europe", November 12-13, 2008, venue: Istanbul Technical University, Faculty of Architecture, 2008)
Kamberidou, I. (2008). ‘Eliminating the Leaky Pipeline: Sustaining-Normalizing-Engendering Women's Careers as Academics, Researchers and Professionals in Engineering, Computers and the Sciences’. Presentation at the UNICAFE Dissemination Conference "Beyond the Glass Ceiling: Women Academics in Engineering, Technology and Life Sciences across Europe", November 12-13, 2008, venue: Istanbul Technical University, Faculty of Architecture. Sixth Research Framework Programme of the European Union SAS6-CT-2006-036695 (http://www.womenacademics2008org). ------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------- My presentation discusses the obstacles that female students face as they attempt to access higher education and achieve success and propose an action plan. Such an action plan requires  Innovative strategies that facilitate academic achievement;  teacher-training to learn innovative, practical and successful  strategies that can be implemented at their institutions  that will enable them to help women students  overcome obstacles on their  path towards a college degree; promoting institutional policies that support retention efforts; financial aid; developing corporate and community partnership; creating a campus atmosphere that promotes engagement and success, among other things  Focusing on the factors that contribute to Greek women’s non-engagement and under-representation in engineering and technology, and in particular the technological gender gap or digital divide in the knowledge economy, this presentation will examine the ‘gendered’ educational institutions in Greece while providing an overview of the gender distribution in the Greek academia.  Undeniably, the overall participation of women in engineering, science and technology is low. Women still comprise a minority in the Greek academia, and especially in the higher academic hierarchies. The ‘genderedness’ of educational institutions in Greece, traditional perspectives, the glass ceiling, the leaky pipeline, the life/work balance or rather imbalance, the lack of affordable child care facilities, among other things, have contributed to the declining interest of women for engineering and technology study programs. Irrefutably education is the place to start, given that socially inclusive educational systems and equity policies are key variables to responding to global change, however it is not enough. Promoting new pedagogical applications as well as recruiting or recognizing the largely untapped pool of talent  What is vital is retention. Retaining, women in their careers in engineering, in science and technology, and in R&D, in addition to increasing their participation in leadership— from decision-making to execution phases— in the light of demographic pressures, aging populations and the low levels of immigration tolerance around Europe. Retention requires the establishment of nurturing inclusive workplace cultures, supportive and socially inclusive working environments, the application of best practices, sustainable diversity efforts and ‘sensitivity’ training to raise awareness. Enhancing conditions for research and innovation in Europe calls for inclusive organizational cultures that allow women to function at their full potential for the benefit of their organization/institution, thereby reproducing female participation.